Rotated DFT‐s‐OFDM for transmitting PAPR‐minimised BPSK symbols. Issue 24 (3rd November 2020) - Cho, L.; Huang, W.; Hsu, C.‐Y.
Abstract : The third generation partnership project has recommended π /2‐binary phase‐shift keying (BPSK) in discrete‐Fourier‐transform‐spread orthogonal frequency division multiplexing (DFT‐s‐OFDM) for low peak‐to‐average power ratio (PAPR) uplink transmission. Recently, the rotation angle of 7 π /6 for rotated BPSK has been proposed by J. Kim et al. to achieve optimal PAPR performance. However, the authors discovered that this angle might negate the contribution to PAPR reduction in most number of allocated subcarriers owing to the discrete‐Fourier‐transform (DFT) boundary‐matching problem. To solve this issue, they propose a novel scheme to fine‐tune the rotation angle to approximately 7 π /6 in a manner compatible with the long‐term evolution/new radio specification, while ensuring that the data phase matches the periodicity. Simulations show that the proposed scheme can stably improve the PAPR by ∼0.2 dB compared to π /2‐BPSK for any DFT spacing, thereby benefiting user equipment by providing better power efficiency and wider signal coverage without additional computational complexity.